2017
DOI: 10.1017/s0007114517000666
|View full text |Cite
|
Sign up to set email alerts
|

Associations between motives for dish choice during home-meal preparation and diet quality in French adults: findings from the NutriNet-Santé study

Abstract: A number of motives such as constraints or pleasure have been suggested to influence dish choices during home-meal preparation. However, no study has evaluated how the importance conferred to these motives potentially influence diet quality. The present study aims at investigating the difference in diet quality according to the importance attached by individuals to various dish choice motives. The importance of twenty-seven criteria related to dish choices on weekdays was evaluated among 48 010 French adults f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Tools used in these studies to measure eating pleasure are presented in Table 5. Eating pleasure was measured using a variety of tools, namely interviews (n = 2) [89,137], pairing and categorization tasks (n = 1) [26], single items (n = 11) [28,29,76,109,111,140,141,147,148,152,160], multi-item questionnaires developed by authors for the purpose of the study (n = 8) [21,74,112,136,145,148,150,156], adapted versions of existing multi-item questionnaires (n = 7) [13,[33][34][35]75,157,158] or existing multi-item questionnaires (n = 13) [21,25,27,30,36,74,84,86,88,125,126,146,151]. In total, 37 different tools were used to measure eating pleasure: 1 interview process, 2 pairing and categorization tasks, 15 single items and 19 questionnaires.…”
Section: Q2 Links Between Eating Pleasure and Dietary Behavior/healtmentioning
confidence: 99%
See 4 more Smart Citations
“…Tools used in these studies to measure eating pleasure are presented in Table 5. Eating pleasure was measured using a variety of tools, namely interviews (n = 2) [89,137], pairing and categorization tasks (n = 1) [26], single items (n = 11) [28,29,76,109,111,140,141,147,148,152,160], multi-item questionnaires developed by authors for the purpose of the study (n = 8) [21,74,112,136,145,148,150,156], adapted versions of existing multi-item questionnaires (n = 7) [13,[33][34][35]75,157,158] or existing multi-item questionnaires (n = 13) [21,25,27,30,36,74,84,86,88,125,126,146,151]. In total, 37 different tools were used to measure eating pleasure: 1 interview process, 2 pairing and categorization tasks, 15 single items and 19 questionnaires.…”
Section: Q2 Links Between Eating Pleasure and Dietary Behavior/healtmentioning
confidence: 99%
“…Dietary behavior and health outcomes for each study are presented in Table 5. Of the 45 studies identified, 31 (68.9%) included only dietary outcomes [7,13,[25][26][27][28][29]33,34,37,75,76,84,86,88,109,111,125,126,136,140,[145][146][147][148][150][151][152]159,160,161], 10 (22.2%) only health outcomes [30,35,36,74,89,112,137,[156][157][158] and 4 (8.9%) included both dietary and health outcomes [21,31,32,141].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations